2018
DOI: 10.1166/jbn.2018.2515
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of 5-Flurouracil into PLGA Nanofibers and Enhanced Anticancer Effect in Combination with Ajwa-Dates-Extract (Phoenix dactylifera L.)

Abstract: Side effects connected with chemotherapeutic agents used in cancer treatment has led to alternative modalities of combinatorial therapies in an attempt to reduce the drug dosage and associated risks. In the current study we evaluated the potential use of Ajwa Dates Extract (ADE), reported to have anti-cancer effects, as an adjuvant therapy in combination with 5-flurouracil (5FU) against the human-breast-adenocarcinoma cell line (MFC-7) in vitro. The effects of ADE alone and in combination with 5-FU were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In addition, growth factors and drugs can be encapsulated due to high surface area and porosity of the electrospun meshes [12][13][14] . In electrospinning, the drugs can be uniformly dispersed into the nano/micro sized fibrous polymer mesh without aggregation and quantitative loss 11,15 . Moreover, adaptability of the electrospinning facilitates desirable drug loading/release by providing different drug loading approaches 13,[16][17][18] .…”
mentioning
confidence: 99%
“…In addition, growth factors and drugs can be encapsulated due to high surface area and porosity of the electrospun meshes [12][13][14] . In electrospinning, the drugs can be uniformly dispersed into the nano/micro sized fibrous polymer mesh without aggregation and quantitative loss 11,15 . Moreover, adaptability of the electrospinning facilitates desirable drug loading/release by providing different drug loading approaches 13,[16][17][18] .…”
mentioning
confidence: 99%
“…Date fruits have been consumed in Arab and its neighboring areas since time immemorial as part of the essential diet. Recent research has shown the anticancer potential of Ajwa dates extract in combination with 5-fluorouracil against human breast adenocarcinoma cell line MCF-7 9 and apoptosis-inducing effect and cell cycle arrest in prostate cancer cells PC3 10 . The ethnopharmacological significance of date palm is well- described in terms of its antioxidant, anti-inflammatory and antitumoral activities against breast carcinoma cells 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is emerging for the cardioprotective effects of Ajwa date (Al-Yahya et al, 2016;Khan and Siddiqui, 2017). Anticancer effects of Ajwa date have been demonstrated in rodent models (Khan et al, 2018) and cancer cell lines for breast (Khan et al, 2016), prostate (Mirza et al, 2018) and colon (Eid et al, 2014) cancers. Other effects include liver (Sheikh et al, 2014), gut (Eid et al, 2014), tissue (Ragab et al, 2013) and kidney (Ali et al, 2011) protection.…”
Section: Introductionmentioning
confidence: 99%